Isotherms, kinetics and thermodynamics of hexavalent chromium removal using biochar. Issue 2 (April 2018) - Choudhary, Bharat; Paul, Debajyoti
Highlights: Eucalyptus globulus bark biochar (EBB) efficiently applied for aqueous Cr(VI) removal. Cr(VI) removal data were evaluated by two- and three-parameter isotherm models. Kinetic data suggest Cr(VI) removal dominantly controlled by film diffusion. Relatively good Cr(VI) sorption capacity of 21.3 mg/g achieved by EBB at 303 K. Negative ΔG° confirm spontaneous Cr(VI) sorption dominated by physisorption. Abstract: This study investigates the isotherm and kinetics of aqueous Cr(VI) removal using Eucalyptus globulus bark biochar (EBB) produced by pyrolysis of residual bark biomass at 500 °C. Various experimental parameters such as Cr(VI) initial concentration (range of 1–240 mg/L), reaction time (15–240 min) and temperature (303–323 K) were studied to understand the EBB–mediated Cr(VI) removal using two–parameter and three–parameter isotherms, sorption kinetics, and thermodynamics. Our data suggest that adsorption of Cr(VI) on biochar follow both Langmuir and Temkin isotherms; the estimated maximum removal capacity is 21.3 mg/g. The estimated Δ H ° (12.07 kJ/mol) and Δ S ° (110 J/mol–K) indicate endothermic and physical nature of sorption, and enhanced randomness at the sorbate–sorbent interface. The negative Δ G ° values (−21.19 to −23.39 kJ/mol at 303–323 K) confirm spontaneous sorption dominated by physisorption. Cr(VI) removal kinetic was governed by the pseudo–second order rate with Cr(VI) removal by EBB dominantly controlled by film diffusion. Our results also show that Cr(VI) removal using EBB was unaffected in the presence of high concentration (800–5000 mg/L) of foreign ions compared to the control experiment. Thus, the developed low–cost EBB seems promising for Cr(VI) removal from various industrial wastewater sources.